THE CONCEPT OF BEAUTY AND NATURE IN GEORGE SANTANA - Houria Belbachir,; Mohamed Bouchiba, (International Journal of Innovative Technologies in Social Science, 2025)
Aesthetics studies and investigates the principles of creativity on which art is based, whether it is visual, cinematic, musical, or literary - be it poetry, a story, or a play. It also examines how our thoughts, feelings, and attitudes are shaped by the experience gained through natural objects, phenomena, and our surroundings. However, defining the concept of beauty is challenging, as its interpretation varies according to the cultural background of the recipient of the work.